2007
DOI: 10.1002/hyp.6773
|View full text |Cite
|
Sign up to set email alerts
|

Hyporheic and total transient storage in small, sand‐bed streams

Abstract: Abstract:Key processes in stream ecosystems are linked to hydraulic retention, which is the departure of stream flow from ideal 'plug flow', and reflects fluid movement through surface and hyporheic storage zones. Most existing information about hyporheic exchange is based on flume studies or field measurements in relatively steep streams with beds coarser than sand. Stream tracer studies may be used to quantify overall hydraulic retention, but disaggregation of surface and hyporheic retention remains difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 41 publications
8
70
1
Order By: Relevance
“…Downstream of a dam, the lower stream stage created an area of low hydraulic head and a pathway for water to come back into the stream. Other researchers have also shown VHG's indicating a downwelling-upwelling flow pathway underneath beaver and debris dams (White, 1990;Stofleth et al, 2008). Such a flow pattern was not observed at the undammed site C.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Downstream of a dam, the lower stream stage created an area of low hydraulic head and a pathway for water to come back into the stream. Other researchers have also shown VHG's indicating a downwelling-upwelling flow pathway underneath beaver and debris dams (White, 1990;Stofleth et al, 2008). Such a flow pattern was not observed at the undammed site C.…”
Section: Discussionmentioning
confidence: 83%
“…Beaver dams are one such biological factor that is rarely studied in spite of their ubiquitous presence and long history of damming streams in North America and Eurasia (Naiman et al, 1988;Baker and Hill, 2003;Rosell et al, 2005). The few studies that have been conducted have focused on how beaver dams restructure flow directions (White, 1990;Stofleth et al, 2008) such that beaver damdriven hyporheic flowpaths become comparable to those at severe meanders along gaining stream reaches and result in water loss to the groundwater system along static to losing stream reaches Hill and Duval, 2009). Water fluxes along these beaver dam-driven hyporheic flow pathways are infrequently quantified, although they influence the flux of dissolved solutes across the stream-groundwater interface, and ultimately downstream water quality.…”
Section: Introductionmentioning
confidence: 99%
“…Wood pieces provide stable substrate for invertebrates and biofilms, entrap leaves and other organic matter, afford overhead cover for fish, promote hyporheic exchange flow and transient storage, enhance hydraulic heterogeneity, and encourage pool formation and channel meandering [Angermeier and Karr, 1984;Beechie and Sibley, 1997;Gregory et al, 2003;Johnson et al, 2003;Mutz and Rohde, 2003;Eggert and Wallace, 2007;Stofleth et al, 2008]. The frequency and character of wood inputs varies in space and time [Latterell and Naiman, 2007;Golladay et al, 2007] and is strongly affected by riparian management [Flebbe and Dolloff, 1995;Angradi et al, 2004;Kreutzweiser et al, 2005;Czarnomski et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Under a temporal perspective, Wondzell (2006) observed that, although the lowland stream is sensitive to changes in wood delivery with a decrease of HEF, over longer time scale large-scale channel adjustments reverse the effect of wood removal causing higher HEF fluxes. In the long term, wood removal results in 10 longer mean residence times, which impacts many hyporheic functions: temperature, nutrient retention, and oxygen concentrations (Sawyer and Cardenas, 2012;Stofleth et al, 2008). In upland rivers, wood typically creates steeper head gradients that drive hyporheic flow paths (Krause et al, 2014) (Fig.…”
Section: Logjams In Large Alluvialmentioning
confidence: 99%